2023
DOI: 10.3390/fractalfract7060459
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Complexity of a New Biparametric Family of Fourth Optimal Order Based on the Ermakov–Kalitkin Scheme

Abstract: In this paper, we generalize the scheme proposed by Ermakov and Kalitkin and present a class of two-parameter fourth-order optimal methods, which we call Ermakov’s Hyperfamily. It is a substantial improvement of the classical Newton’s method because it optimizes one that extends the regions of convergence and is very stable. Another novelty is that it is a class containing as particular cases some classical methods, such as King’s family. From this class, we generate a new uniparametric family, which we call t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is because in practice, it has been observed that iterative schemes that are stable for such functions tend to perform better compared to other methods that exhibit some pathology when applied to more complicated functions. To this end, complex discrete dynamics are employed to analyze stability in functions like quadratic polynomials (see, for example, the work of Amat et al in [1,2], Behl et al in [3], Chicharro et al in [9], Cordero et al in [15][16][17]), Khirallah et al [22], Moccari et al in [25], among others.…”
Section: Introduction and Preliminary Conceptsmentioning
confidence: 99%
“…This is because in practice, it has been observed that iterative schemes that are stable for such functions tend to perform better compared to other methods that exhibit some pathology when applied to more complicated functions. To this end, complex discrete dynamics are employed to analyze stability in functions like quadratic polynomials (see, for example, the work of Amat et al in [1,2], Behl et al in [3], Chicharro et al in [9], Cordero et al in [15][16][17]), Khirallah et al [22], Moccari et al in [25], among others.…”
Section: Introduction and Preliminary Conceptsmentioning
confidence: 99%